Parental preference in the selection of a preschool - Ruiz, Ma. Emerita C. (2000)
School has become the main concern of parents even before elementary age. A lot of children below six years are now enrolled in a preschool. Because of the numerous schools available, one may wonder how a parents choose school for their preschool-aged child. This study looked into the different factors which has influenced the parents in the selection of a preschool for their children. It assessed four major factors: a) program; b) facilities and services; c) staff competence; and d) affordability which parents may have considered before finally selecting the school. The researcher developed a three-part questionnaire for this study to get respondents' demographic characteristics, arrangement of factors influencing selection of a preschool, and evaluation of parents' expectations for chosen preschools. Sixty-three parents with children between 4 - 5 years old currently enrolled were randomly selected from two preschools with different approaches of teaching. The demographic data included in the study were: age of respondents, annual family income, educational attainment, occupation, child's age, school preference and, school knowledge. Among the parents' demographic data, associations were found with the factors influencing the selection of preschools with .05 level of significance. There was an association between the program and age of respondents, annual family income, educational attainment, occupation, and school knowledge. Association was present between staff competence and sex of respondents as well as school preference. On the other hand, the factor on facilities and services has an association on the school preference only. For the factor on affordability, an association existed with age of respondents and occupation. The results of this study indicated that for the parents, the most influential factors in their selection of a preschool are staff competence first and school facilities and services second. Under these factors, the underlying items which influenced parents in their selection included competent teachers with a good foundation in early childhood education; the location of the school; the availability of classrooms which were conducive to learning; the accessibility of the school personnel and teaching staff. The factor on program was also very influential but to a lesser degree based on the frequency count. This study found out that while the two preschools differed in their approaches to teaching, parents of both schools were looking for the same outcome in the performance of their children.